Conjugated Polymer with Intrinsic Alkyne Units for Synergistically Enhanced Raman Imaging in Living Cells. (19th September 2017) - Li, Shengliang; Chen, Tao; Wang, Yunxia; Liu, Libing; Lv, Fengting; Li, Zhiliang; Huang, Yanyi; Schanze, Kirk S.; Wang, Shu
Abstract: Development of Raman‐active materials with enhanced and distinctive Raman vibrations in the Raman‐silent region (1800–2800 cm −1 ) is highly required for specific molecular imaging of living cells with high spatial resolution. Herein, water‐soluble cationic conjugated polymers (CCPs), poly(phenylene ethynylene) (PPE) derivatives, are explored for use as alkyne‐state‐dependent Raman probes for living cell imaging due to synergetic enhancement effect of alkyne vibrations in Raman‐silent region compared to alkyne‐containing small molecules. The enhanced alkyne signals result from the integration of alkyne groups into the rigid backbone and the delocalized π‐conjugated structure. PPE‐based conjugated polymer nanoparticles (CPNs) were also prepared as Raman‐responsive nanomaterials for distinct imaging application. This work opens a new way into the development of conjugated polymer materials for enhanced Raman imaging.